Pengaturan Perjanjian Internasional Dan Relevansinya Dengan Klaim Pulau Dokdo Berdasarkan Perjanjian San Fransisco 1951 - Cliff Markus Latumeten; Johanis Steny Franco Peilouw; Lucia Charlota Octovina Tahamata (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Dokdo Island dispute is one of the disputes involving Japan and South Korea. Both Japan and South Korea still hold fast that Dokdo Island is part of their country's sovereignty.Purposes of the Research: The purpose of this paper is to find out and examine the arrangement of international agreements in claiming an area as well as to find out and examine the settlement of claims made by Japan against Dokdo Island based on the 1951 San Francisco Agreement. Methods of the Research: The type of research used in this research is normative juridical (normative legal research type), which is an approach that is carried out by researching or studying well library materials or literature studies. Especially to examine the provisions of positive law, legal principles, legal principles, and international law doctrines in order to answer the legal issues faced.Results of the Research: The results of this study indicate that the emphasizes that an international treaty dispute must be resolved by peaceful means in accordance with the principles of justice and international law. The 1951 San Francisco agreement itself does not explain the arrangement of international agreements in claiming an area, either directly or indirectly bordering areas. Because the San Francisco agreement itself was a peace treaty between Japan and the Allies to end World War II. Various dispute resolution efforts have been carried out such as diplomatic and judicial settlements, but until now the right way to resolve the Dokdo Island dispute has not been found. Based on the contents of the 1951 San Francisco Agreement, there was no discussion related to the settlement of the Dokdo island dispute between Japan and South Korea or other international disputes because the agreement was only a peace agreement between Japan and its allies in ending World War II. However, there are several ways of resolving disputes that can be taken by both parties, both through non-litigation and litigation channels, such as through mediation, negotiation to settlement through the International Court of Justice.